A Study On Perception Of Freight Forwarders Towards Third Party Logistics With Reference To Everon Impex (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Outsourcing of logistics function is a business dynamics of growing importance all over the world. A growing awareness that competitive advantage comes from the delivery process as much as from the product has been instrumental in upgrading logistics from its traditional backroom function to a strategic boardroom function. In order to handle its logistics activities effectively and efficiently, a company may consider the following options – it can provide the function in-house by making the service, or it can own logistics subsidiaries through setting up or buying a logistics firm, or it can outsource the function and buy the service. Currently, there has been a growing interest in the third option, i.e. outsourcing of logistics functions to third party logistics service providers. The main objectives of the study is to know the perception of employees towards third party logistics. For this purpose a sample of 75 was collected from the respondents and the respondents are those who are employees working with various companies. Based on the findings it is concluded that though the usage of 3PL services reveals positive and significant impact on business performance, third party logistics practices are still at a nascent stage with the companies.Organizations will increase the usage of 3PL services in traditional logistics activities and increase the scope of outsourcing based on the overall satisfaction and the impact on business objectives – logistics system performance, customer satisfaction and employee morale.